Squalius cephaloides, a synonym of Squalius cii (Teleostei: Leuciscidae) - Bayçelebi̇, Esra; Turan, Davut; Aksu, İsmai̇l; Freyhof, Jörg (Zootaxa, 2022)
The ‘two species’ hypothesis for S. cephaloides and S. cii, both occurring in the southern Marmara Sea basin, is tested. Our results suggested that there are no morphological and molecular characters to support this hypothesis, and we treat Squalius cephaloides as a junior synonym of S. cii.